Credit Demand among Small Farmers: A District Level Approach, Pakistan - Raza , Ali (Asian Journal of Agriculture and Rural Development, 2019)
In the current study, determinants of credit demand among small farmers in the Mandi Bahauddin district of Pakistan were investigated. For this purpose, interviews with 123 small farmers in six villages of this district were conducted. Both qualitative and quantitative techniques were used to examine factors that affect credit demands. Seven determinants were devised and tested, and a probit model was employed to analyze the effects of education, household size, and income on the credit demand. Through qualitative methods, factors like informal lending, interest rate, consumption smoothing, and transaction cost were analyzed. It was noted that informal borrowing, higher interest rates, and high transaction costs crowded out formal lending. A positive correlation was observed between education and credit demand. Household size and all types of incomes did not significantly correlate with credit demand.